Pelatihan Pengembangan Subject Spesific Pedagogi Tematik Berbasis TPACK Bagi Guru SD Muhammadiyah di Wilayah Sleman Yogyakarta - Fitri Indriani; Nur Hidayah; Yayuk Hidayah (Prima Abdika : Jurnal Pengabdian Masyarakat, 2021)
This community service activity aims to increase the understanding of Muhammadiyah Elementary School teachers in the Sleman Yogyakarta Region regarding the development of specific subject-specific thematic pedagogy based on TPACK. This activity was carried out online using Zoom Meeting involving 79 Muhammadiyah Elementary School teachers in the Sleman Region of Yogyakarta. Service activities are carried out through lectures, questions and answers and performances. After this service activity has been carried out, it shows that 1) in developing subject-specific thematic pedagogy based on TPACK for Muhammadiyah elementary school teachers in the Sleman region of Yogyakarta, it is a learning tool that can encourage students to be more active in collaborating between technology, pedagogics and materials. 2) the development of subject specific thematic pedagogy based on TPACK for Muhammadiyah Elementary School teachers in the Sleman Yogyakarta Region which is carried out online can be effectively carried out with cooperative learning strategies, Project based learning.